Traumatologie aiguë du badminton : étude épidémiologique à propos de 140 cas - Saragaglia, D.; Saliba-Ranson, P.; Banihachemi, J. J. (Science & Sports, 2020)
The main objective of this study was to establish an overview of acute traumatology of badminton in injured people identified in an emergency department specialized in limb trauma. This is a retrospective, mono-centric epidemiological study, in which we included, from January 1, 2010 to January 1, 2015, 135 patients totaling 140 admissions and 146 lesions; 67 (48%) concerned females and 73 (52%) concerned males. The average age was 28 ± 13.8 years ranging from 10 to 66 years. A total of 65% of patients could be contacted by telephone to complete a questionnaire aimed at completing the information in the medical records. A total of 129 lesions (88.3%) were located to the lower limbs, 16 (11%) to the upper limbs, and one (0.7%) to the head. These were 87 sprains (59.6%), 34 tendino-muscular lesions (23.5%), 13 fractures (8.9%), 5 dislocations (3.4%), 3 hyperalgesic contusions (2.1%), 3 meniscal injuries (2.1%) and a wound. In the lower limbs, lateral ankle sprains were the most frequent (50.5%), followed by ruptures of the Achille tendon (14%), tennis legs (8.5%) and mid-tarsal sprains (7%). Of the 146 lesions, 118 (81%) received non-operative treatment and 28 (19%) received surgical treatment. Lateral ankle sprains, as well as tendino-muscular lesions of the calf are, by far, the most frequent lesions of badminton. A modification of the shoe of the badminton player should be considered to decrease the frequency of the ankle injuries, which is exceptionally high.